Pengaturan Rapat Umum Pemegang Saham Dalam Anggaran Dasar Perseroan Terbatas - Anak Agung Ngurah Bagus Wiradhanta Adipratama (Jurnal Hukum Sasana, 2022)
The RUPS has the right to obtain all the exclusive powers of the RUPS as stipulated in the Company Law and cannot be waived as long as there are no changes to the Company Law. Meanwhile, the exclusive authority in the articles of association is solely based on the will of the RUPS which is ratified and approved by the Minister of Justice which can be changed through amendments to the articles of association as long as it does not conflict with the Company Law. Regulation of RUPS In PT is regulated, Article 94, 102 and Article 104. Company Law No. 40 of 2007 appoints members of the Board of Directors, and determines certain restrictions for the Board of Directors that require RUPS approval. Article 63 of the Company Law states that the RUPS has all powers not granted to the Board of Directors. or Commissioner Article 69, all activities including approval of financial statements and ratification of financial statements as well as reports on the supervisory duties of the Board of Commissioners are carried out by the General Meeting of Shareholders. Article 64 of Law No.1 of 1995 as amended by Article 76 of Law No.1 of 2007 concerning Limited Liability Companies, determines the location of the RUPS. Paragraph (1) states that the RUPS is held at the domicile of the company or where the company conducts its business activities, unless otherwise stipulated in the Articles of Association. The place as referred to in paragraph (1) must be located in the territory of the Republic of Indonesia [paragraph (2)]. So the RUPS cannot be held outside the territory of the Republic of Indonesia, even though, for example, the limited liability company in question is 100% owned by foreign investors.